Association between walking speed and age in healthy, free-living individuals using mobile accelerometry--a cross-sectional study. - Michaela Schimpl; Carmel Moore; Christian Lederer; Anneke Neuhaus; Jennifer Sambrook; John Danesh; Willem Ouwehand; Martin Daumer (PLoS ONE)
Context Walking speed is a fundamental parameter of human motion and is increasingly considered as an important indicator of individuals' health status. Objective To evaluate the relationship of gait parameters, and demographic and physical characteristics in healthy men and women. Design, setting, and participants Recruitment of a subsample (n = 358) of male and female blood donors taking part in the Cambridge CardioResource study. Collection of demographic data, measurement of physical characteristics (height, weight and blood pressure) and assessment of 7-day, free-living activity parameters using accelerometry and a novel algorithm to measure walking speed. Participants were a median (interquartile range[IQR]) age of 49 (16) years; 45% women; and had a median (IQR) BMI of 26 (5.4). Main outcome measure Walking speed. Results In this study, the hypothesis that walking speed declines with age was generated using an initial 'open' dataset. This was subsequently validated in a separate 'closed' dataset that showed a decrease of walking speed of -0.0037 m/s per year. This is equivalent to a difference of 1.2 minutes, when walking a distance of 1 km aged 20 compared to 60 years. Associations between walking speed and other participant characteristics (i.e. gender, BMI and blood pressure) were non-significant. BMI was negatively correlated with the number of walking and running steps and longest non-stop distance. Conclusion This is the first study using accelerometry which shows an association between walking speed and age in free-living, healthy individuals. Absolute values of gait speed are comparable to published normal ranges in clinical settings. This study highlights the potential use of mobile accelerometry to assess gait parameters which may be indicative of future health outcomes in healthy individuals.